The Economic Value of Social and Emotional Learning. Issue 3 (2015) - Belfield, Clive; Bowden, A. Brooks; Klapp, Alli; Levin, Henry; Shand, Robert; Zander, Sabine
Abstract : There is a growing body of research emphasizing the advantages of teaching students social and emotional (SE) skills in school. Here we examine the economic value of these skills within a benefit-cost analysis (BCA) framework. Our examination has three parts. First, we describe how the current method of BCA must be expanded to adequately evaluate SE skills, and we identify important decisions analysts must make. Second, we review the evidence on the benefits of SE skills, again noting key methodological issues with respect to shadow pricing. Finally, we perform BCA of four selected social and emotional learning (SEL) interventions: 4Rs; Second Step, Life Skills Training; and Responsive Classroom. These analyses illustrate both methodological and empirical challenges in estimating net present values for these interventions. Even with these challenges, we find that the benefits of these interventions substantially outweigh the costs. We highlight promising areas of research for improving the application of BCA to SEL.